ELECTRONIC BANKING: THE NEW FACE OF MODERNIZING THE ALGERIAN SERVICES SECTOR - REALITY AND PROSPECTS - Rahali Seifeddine; Lakehal Nora; Rahali Hadjila (International Journal of Innovative Technologies in Social Science, 2025)
The banking sector is the engine of the economic fabric of countries, so Algeria has worked on successive reforms, the latest of which was the issuance of the Monetary and Banking Law of 2023, as a strategy to diversify the banking operations of banks and financial institutions. The world of banking has witnessed a scientific transformation in terms of the dimensions and objectives of banks’ strategies in the last few decades. This was a logical result of the revolution of new technologies in media and communication and the globalization of the financial and banking markets. Perhaps this is what led banking institutions in particular and financial institutions in general to move towards providing a new type of services in line with what has become characteristic of the banking market. Hence, some believe that banks must develop their performance in line with the surrounding conditions, embodying this development in electronic banking. This study aims to understand the reality of electronic banking in Algeria and the mechanisms for its implementation.